Penguatan Keunggulan Bersaing Berkelanjutan Industri Kreatif Tenun Ikat Bima melalui Integrasi Strategi Digital Green Marketing dan Green Dynamic Capabilities - Fitriani, Fani; Ovriyadin, Ovriyadin (Riwayat: Educational Journal of History and Humanities, 2025)
The creative industry is required to implement environmentally friendly and innovative strategies in response to the growing consumer awareness of sustainability issues. Digital green marketing and green dynamic capabilities are key to strengthening sustainable competitive advantage, particularly for Tenun Ikat Bima SMEs, which possess high cultural and economic value. This study is aligned with the SDGs goals as it promotes SME empowerment, digital-based innovation, and the active role of women in weaving communities. A quantitative approach with a survey method was employed, using a Likert scale questionnaire as the research instrument. The population includes all Tenun Ikat Bima SMEs located in three regions of West Nusa Tenggara Province: Bima City, Bima Regency, and Dompu Regency, with a total of 200 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM-PLS). The results show that digital green marketing and green dynamic capabilities have a significant influence on strengthening the sustainable competitive advantage of Tenun Ikat Bima.